2012
DOI: 10.1016/j.bpj.2011.12.017
|View full text |Cite|
|
Sign up to set email alerts
|

Temperature-Induced Transitions in the Structure and Interfacial Rheology of Human Meibum

Abstract: Meibomian lipids are the primary component of the lipid layer of the tear film. Composed primarily of a mixture of lipids, meibum exhibits a range of melt temperatures. Compositional changes that occur with disease may alter the temperature at which meibum melts. Here we explore how the mechanical properties and structure of meibum from healthy subjects depend on temperature. Interfacial films of meibum were highly viscoelastic at 17°C, but as the films were heated to 30°C the surface moduli decreased by more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…Two studies have found that evaporation can be reduced in dry eye (Fujishima et al, 1996; Mori et al, 1997) but these authors point out that their subjects are aqueous deficient dry eyes, and Craig et al (2000) speculate that this may be responsible for the reduced evaporation rate. Leiske et al (2012) and Bron et al (2004) also showed that the temperature dynamics may have an impact on lipid layer dynamics, for example, which have temperature-dependent properties.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Two studies have found that evaporation can be reduced in dry eye (Fujishima et al, 1996; Mori et al, 1997) but these authors point out that their subjects are aqueous deficient dry eyes, and Craig et al (2000) speculate that this may be responsible for the reduced evaporation rate. Leiske et al (2012) and Bron et al (2004) also showed that the temperature dynamics may have an impact on lipid layer dynamics, for example, which have temperature-dependent properties.…”
Section: Discussionmentioning
confidence: 98%
“…Such models could use different properties for the cornea and aqueous humor, as well as for conjunctiva, stroma, and vitreous humor, that are posterior to the tear film. Furthermore, more complex treatments of the tear film, e.g., with separate lipid and aqueous layers, may add additional insights into tear film and OST dynamics, and the OST may be an important input into the properties of the lipid layer (Leiske et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this value might be reduced if there was bending of the cholesterol side chains. It may be noted that small angle X-ray scattering of bulk human meibum 53 indicates multilamellar structures with a lamellar thickness of 4.9 nm, and multilamellar structures of a similar thickness have been demonstrated in meibum spread on saline. 48 It may also be noted that a small quantity of human meibum spread on saline at 20°C (20 μg over 80 cm 2 ) forms a uniform layer (with included “lakes”) of about 5.2 nm thick.…”
Section: Conclusion – Implications For Lipid Layer Structure: a mentioning
confidence: 94%
“…They may also greatly aid in understanding the function and properties of the lipid layer, as well as testing of multilamellar models of the lipid layer structure (King-Smith et al, 2013a; Leiske et al, 2012b; Rosenfeld et al, 2013). Mathematical models may need to incorporate complex surface rheology of the lipid layer as a result of lipid layer structure (Bhamla et al, 2014; Georgiev et al, 2014), but it is unclear at the time of writing how much of the in vivo elastic properties at room temperature remain at physiological temperatures (Leiske et al, 2012a). …”
Section: Summary and Future Directionsmentioning
confidence: 99%